Impact of Risk Perception on Surfers' Intention to Revisit is Mediated by Emotion and Experience Quality - Chen Yangle; Cui Wenxin (Redai dili, 2023)
Globally, the surfing tourism industry has matured, as has the research in this sector. In recent years, surfing tourism in China has been favored by domestic risk preference tourists because it can meet the demand for adventure sports tourism, and a number of surfing tourism resorts have emerged. However, domestic-related theoretical research is obviously insufficient. Utilizing the theories of risk edge and emotion evaluation theory and taking Riyue Bay, Wanning City (Hainan Province) as the research area, tourists were surveyed in order to ascertain emotion and experience as factors to incorporate in a structural equation model. The intermediary effect analysis method was applied to explore the impact mechanism of risk perception on the intention of surfing tourists to revisit, in order to provide theoretical support and countermeasures for the sustainable development of domestic surfing tourism. The data collected in this study were verified as representational, reliable, and effective, and the model fitted the data well. Based on the results, the following two conclusions can be drawn. 1) On the one hand, risk perception has a significant direct and positive impact on emotional arousal of the surfer, and emotion plays a completely intermediary role in the impact of risk perception on intention to revisit; that is, risk perception has no significant direct impact on intention to revisit, which is in agreement with some studies and contradicts others. On the other hand, experience quality plays an intermediary role in the influence of emotion on revisit intention, and the intermediary effect is slightly higher than the direct effect. These conclusions indicate that surfing tourism operators should not only fully mobilize the positive emotions of surfers, but also find ways to let surfers obtain a higher-quality surfing tourism experience to better attract repeat visitors. In order to promote the sustainable development of surfing tourism in Riyue Bay, Wanning City, we make the following suggestions. First, risk preference tourists should be considered the main target audience in marketing. Second, management norms should be established for surfing clubs (stores) and evaluation mechanisms for surfing coaches. Third, safety supervision should be strengthened to enhance the surfing experience. Lastly, surfers should be helped to successfully surf and stimulate positive emotions. Although there are still some limitations, these preliminary results advance the field of risk perception in tourism, both in theory and in practice.